Theoretical insight of stabilities and optoelectronic properties of double perovskite Cs2CuIrF6: Ab-initio calculations - Caid, Messaoud; Rached, Youcef; Rached, Djamel; Rached, Habib (Journal of molecular modeling, 2023)
Context In this study, we predict the stability, elastic, electronic and optical properties of double perovskite (DP) Cs 2 CuIrF 6 . The detailed investigation of electronic structure and optical properties to find the suitability of DP Cs 2 CuIrF 6 for device applications. From the structural optimization results, the stability of DP (Cs 2 CuIrF 6 ) is in cubic order and belongs to the Fm-3 m space group (#225) with a nonmagnetic (NM) state. Additionally, the elastic results show that this DP is mechanically stable in a cubic and ductile manner. Further, we explain in detail the semiconducting nature of the proposed DP with the help of electronic structure and density of states (DOS). The electronic band gap of DP Cs 2 CuIrF 6 is 0.72 eV (L V -X C ). The optical part discussion, like the dielectric function ε, reflectivity R, refractive index n, absorption coefficient α and optical conductivity σ up to 13.00 eV. The studied compound is explored as a potential candidate for optoelectronic applications. Methods The density functional theory (DFT) within generalized gradient approximation (GGA) scheme of Perdew, Burke and Ernzerhof (PBE) as implemented in Wien2k computational code is utilized to achieve stable structure, elastic, electronic and optical properties of this material. The dynamic stability of this material was studied using the finite displacement method implemented in the CASTEP computational code. The elastic results have been computed by the IRelast package implemented in the Wien2k computational code.